2010
DOI: 10.1097/ede.0b013e3181f20e6c
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Primary and Secondary Organic Aerosols With Airway and Systemic Inflammation in an Elderly Panel Cohort

Abstract: Background Exposure-response information about particulate air-pollution constituents is needed to protect sensitive populations. Particulate matter <2.5 mm (PM2.5) components may induce oxidative stress through reactive-oxygen-species generation, including primary organics from combustion sources and secondary organics from photochemically oxidized volatile organic compounds. We evaluated differences in airway versus systemic inflammatory responses to primary versus secondary organic particle components, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 41 publications
9
136
2
1
Order By: Relevance
“…For average exposures of 273 ng/m 3 -that is, occupational exposures considerably higher that environmental levels -the RR was 1.64 (95% CI: 1.13-2.38). PAHs were also associated with increased systemic inflammation, which explained the association with quasiultrafine particle mass from traffic emission sources, more so that other organic components of PM (Delfino et al, 2010b). Another study found an association between PM, particle-bound organic compounds (including PAHs) and adverse health symptoms in survivors of myocardial infarctions (Kraus et al, 2011).…”
Section: Rationalementioning
confidence: 96%
See 2 more Smart Citations
“…For average exposures of 273 ng/m 3 -that is, occupational exposures considerably higher that environmental levels -the RR was 1.64 (95% CI: 1.13-2.38). PAHs were also associated with increased systemic inflammation, which explained the association with quasiultrafine particle mass from traffic emission sources, more so that other organic components of PM (Delfino et al, 2010b). Another study found an association between PM, particle-bound organic compounds (including PAHs) and adverse health symptoms in survivors of myocardial infarctions (Kraus et al, 2011).…”
Section: Rationalementioning
confidence: 96%
“…A series of panel studies have reported that while total organic carbon has not been associated with the outcomes, associations have been observed for primary organic carbon (and not secondary organic carbon compounds) (Delfino et al, 2009b;. In one study, primary organic carbon was associated with markers for systemic inflammation, whereas secondary organic carbon was associated with a marker for pulmonary inflammation (Delfino et al, 2010b).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary particles, organic markers, ultrafine particles, CO, and NO x were positively associated with IL-6. Reactive oxygen species were associated with both outcomes [Delfino et al, 2010].…”
Section: Pulmonary and Systemic Oxidative Stress And Inflammation: Pomentioning
confidence: 96%
“…Tel. : 1-213-740-6134;Fax: 1-213-744-1426 E-mail address: sioutas@usc.edu size allowing for deep penetration into the lungs and subsequently the bloodstream (Brugge et al, 2007;de Kok et al, 2006;Delfino et al, 2010). PM 2.5 is composed of several chemical species, including carbonaceous materials such as elemental and organic carbon (EC/OC), crustal elements, organic compounds, transition metals, hopanes and steranes, and vehicular abrasion detritus.…”
Section: Introductionmentioning
confidence: 99%